STEAM or not STEAM: Delving into Teacher’s Planning in Early Child Bilingual Education - Ni Putu Wismayani Pratiwi; Made Hery Santosa (Cetta: Jurnal Ilmu Pendidikan, 2021)
This study aims at analyzing the extent to which the weekly planning by playgroup teacher in a bilingual early childhood education reflects on STEAM. This was qualitative research that involved a female playgroup teacher who teaches in a bilingual early childhood education in Denpasar, Bali. Meanwhile, the object of this research was 39 weekly plans with 15 themes in the academic year of 2020/2021. There were two methods of data collection used in this study, such methods as document analysis and interview. The instruments used were analysis form checklist and interview guide The weekly plans were analyzed by the document analysis method to determine the extent to which STEAM was reflected in the weekly plan. Meanwhile, a one-on-one interview was conducted to obtain data on teacher knowledge about STEAM. The results of this study found that all of the weekly plans reflected on STEAM. Even though each aspect STEAM was not evenly distributed since the goal of the school focuses on pre-literacy and pre-numeracy. Therefore, Science and Math were mostly appeared in the teacher’s planning. Furthermore, it was obtained from the interview that the teacher had a good comprehension about STEAM and its implementation. This study gives an insight to the other playgroup teachers about how to integrate STEAM in their planning. However, this research was conducted on a small scale and without classroom observations. Further research is expected to be carried out on a large scale and by observing the class.